Shakespeare and the medieval world - Cooper, Helen (Arden Critical Companions, 2010)
A unique study examining the influence of medieval culture, thinking and drama on Shakespeare's work, looking at his use of sources and the ways in which the traditions of medieval drama permeate his plays.